2020
DOI: 10.3389/fnins.2020.00443
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 at the Interface Between Peripheral and Central Immune Function in Parkinson’s

Abstract: It is becoming increasingly accepted that there is an interplay between the peripheral immune response and neuroinflammation in the pathophysiology of Parkinson's disease (PD). Mutations in the leucine-rich-repeat kinase 2 (LRRK2) gene are associated with familial and sporadic cases of PD but are also found in immune-related disorders, such as inflammatory bowel disease (IBD) and leprosy. Furthermore, LRRK2 has been associated with bacterial infections such as Mycobacterium tuberculosis and Salmonella typhimur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 161 publications
2
68
0
Order By: Relevance
“…The current study adds further support to the hypothesis suggesting an involvement of the peripheral and central immune system in PD. On top of the HLA locus, several other genes with potential roles in the immune system, including LRRK2 and potentially BST1 , 8, 10 have been implicated in PD. 7 In the periphery, there are notable changes in the immune system of PD patients compared to controls, as peripheral monocytes have differential expression of immune related proteins and markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study adds further support to the hypothesis suggesting an involvement of the peripheral and central immune system in PD. On top of the HLA locus, several other genes with potential roles in the immune system, including LRRK2 and potentially BST1 , 8, 10 have been implicated in PD. 7 In the periphery, there are notable changes in the immune system of PD patients compared to controls, as peripheral monocytes have differential expression of immune related proteins and markers.…”
Section: Discussionmentioning
confidence: 99%
“…4, 5 Genetic evidence also links the immune system with PD, since genes such as LRRK2 , the HLA locus and possibly BST1 , all associated with PD 7 and have a role in the immune system. 8-10…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in LRRK2 ( PARK8 ) gene are the most common genetic cause of both familial and sporadic PD [ 132 ]. Besides PD, mutations in the LRRK2 gene are also found in immune-related disorders, such as inflammatory bowel disease (IBD) and some bacterial infections [ 133 ]. In a genome-wide association study, it was also reported that LRRK2 mutations are associated with autoimmune diseases such as type 1 diabetes, Crohn disease, ulcerative colitis, rheumatoid arthritis, celiac disease, psoriasis, and multiple sclerosis [ 134 ].…”
Section: Genomics Of Pd-related Inflammationmentioning
confidence: 99%
“…Therefore, LRRK2 seems to participate in the regulation of inflammatory responses not only in the brain but also at a systemic level. In fact, LRRK2 expression is expressed in microglia but also in peripheral immune cells such as monocytes, neutrophils, dendritic cells and, to a lower extent, in B and T cells [ 133 , 135 ]. LRRK2 modulates several pathways in innate and adaptive immunity by interfering with NF-κB and NF-AT signaling [ 136 ].…”
Section: Genomics Of Pd-related Inflammationmentioning
confidence: 99%
“…49 Inflammatory cytokine secretion from monocytes is greater in iPD patients than in controls and correlates with LRRK2 expression in T cells in iPD patients (but not controls). 49 These findings suggest that the function of LRRK2 in immune cells is altered in iPD and should be considered in research regarding the role of LRRK2 in iPD pathogenesis (reviewed in Wallings et al 51 ). Furthermore, when assessing therapies to target LRRK2, it is important to consider that the function of LRRK2 is highly cell-type-dependent and poorly understood.…”
Section: Lrrk2mentioning
confidence: 99%